Laboratory evaluation of climbing helmets: assessment of linear acceleration. (1st March 2023) - Begonia, Mark; Rowson, Bethany; Scicli, Black; Goff, John Eric
Abstract: This study utilized a guided free-fall drop tower and standard test headform to measure the peak linear acceleration (PLA) generated by different climbing helmet models that were impacted at various speeds (2–6 m s −1 ) and locations (top, front, rear, side). Wide-ranging impact performance was observed for the climbing helmet models selected. Helmets that produced lower PLAs were composed of protective materials, such as expanded polystyrene (EPS) or expanded polypropylene, which were integrated throughout multiple helmet regions including the front, rear and side. Climbing helmets that produced the highest PLAs consisted of a chinstrap, a suspension system, an acrylontrile butadiene styrene (ABS) outer shell, and an EPS inner layer, which was applied only to the top location. Variation in impact protection was attributed not only to helmet model but also impact location. Although head acceleration measurements were fairly similar between helmet models at the top location, impacts to the front, rear, and side led to larger changes in PLA. A 300 g cutoff for PLA was chosen due to its use as a pass/fail threshold in other helmet safety standards, and because it represents a high risk of severe head injury. All seven helmet models had the lowest acceleration values at the top location with PLAs below 300 g at speeds as high as 6 m s −1 . Impact performance varied more substantially at the front, rear, and side locations, with some models generating PLAs above 300 g at speeds as low as 3 m s −1 . These differences in impact performance represent opportunities for improved helmet design to better protect climbers across a broader range of impact scenarios in the event of a fall or other collision. An understanding of how current climbing helmets attenuate head acceleration could allow manufacturers to enhance next-generation models with innovative and more robust safety features including smart materials.